SSR and morphological traits based fingerprints and DNA barcodes for varietal identification in rice - Rajappa Harisha; Dharavath Bhadru; Satturu Vanisri; Vuppu Gourishanakar; Lakkakula Satish (Biotechnology & Biotechnological Equipment, 2021)
Varietal identification has attained prime importance at a global level particularly in the context of plant variety protection. In this study, forty-six traits were characterized for the establishment of the sheer distinctness among eighteen rice varieties. Morphologically, out of forty-six traits, twenty-five traits did not display any variation among the varieties studied. Significant variations were observed for 21 traits which are relatively more informative in the identification/characterization. Distinctness, uniformity and stability-based fingerprints specific to the studied varieties were developed based on the variations. A total of 175 simple sequence repeat (SSR) markers were screened for polymorphism; 53 hypervariable polymorphic SSR markers were utilized for fingerprinting of rice varieties. A total of 151 alleles were detected in these 53 SSR markers with an amplification size ranging from 120 to 750 bp and the allelic range of 2–4. The average number of alleles observed was 2.84 per locus. The PIC values of 53 SSRs ranged from 0.03 (RM 12983) to 0.64 (RM 11449) with an average of 0.40. The generated allelic variations of 53 SSR markers for the varieties were translated into DNA barcode profiles by separating the allele size from each SSR locus. Multiplex polymerase chain reaction (PCR) with five markers (RM 21392, RM 1388, RM 6699, RM 25754 and RM 16913) was used to identify rice varieties based on the band positions. This study classifies and identifies rice varieties and is an important reference to test the authenticity and varietal purity of other rice varieties in the future. Supplemental data for this article is available online at https://doi.org/10.1080/13102818.2021.1987324 .